Teaching Simple Structure by Using Snakes and Ladders Games to Improve Students’ Speaking Skill - Muhammad Wahyu Hadi; Masyudi - - (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This article discusses teaching strategies in teaching simple structure with snakes and ladders games to improve students’ speaking skill. Specifically, this article presents how teaching through games can improve students’ speaking by using snake and ladder games in simple structure. Teaching English by using board game materials (snakes and ladders) is great for learning English simple structure. This activity allows students to improve their understanding. This game is a simple and fun media for students. It can be found that from observation, questionnaires and writing and speaking exercises in learning English by using the ladder snake game. From the questionnaire data, it can be seen that all student answers that media board games can improve students' speaking ability. The sample of the research is class VII A MTS Sulamul Ma’ad Penujak in academic year 2022/2023 and there are 20 students in this class consisting of 7 male and 13 female. The data collection used direct observation techniques, measurement techniques and documentation techniques. The techniques of data analysis used descriptive and qualitativeIt was found that students enjoy, interesting, learn while playing, effective, understand, think creatively and remember the material. The use of the ladder snake game to teach speaking and writing competence improves students' ability in simple structure. This media is not only easy but also brings many advantages and effectiveness in teaching English. This was seen in the pre-test, cycle I, and cycle II in learning processes. It increased by 40% during the learning process from the pre-test to the Cycle I, taking the overall proportion to 85%. This may be because students are unfamiliar with the learning process by using the games of snakes and ladders. These were well implemented with an average category score of 75.72. The increase in student learning outcomes recorded a 10% increase from Cycle I to Cycle II, while the overall percentage of passing students increased to 85%. In other words, improving student learning outcomes at each level is a good improvement category with an average score of 80.33.Keywords: teaching, simple structure, snakes and ladders, fun, understanding